Repeated cold-water immersion improves autonomic cardiac modulation following five sessions of high-intensity interval exercise - Malta, Elvis Souza [UNESP]; Lopes, Vithor Hugo Fialho [UNESP]; Esco, Michael R.; Zagatto, Alessandro Moura [UNESP] (Springer Nature, 2023)
Purpose: The study aimed to investigate the effect of repeated cold-water immersion (CWI) after high-intensity interval exercise sessions on cardiac-autonomic modulation, neuromuscular performance, muscle damage markers, and session internal load. Methods: Twenty-one participants underwent five sessions of high-intensity interval exercise (6–7 bouts of 2 min; pause of 2 min) over a two-week period. Participants were allocated randomly into either a group that underwent CWI (11-min; 11 °C) or a group that performed passive recovery after each exercise session. Before the exercise sessions were performed, countermovement jump (CMJ) and heart rate variability were recorded (i.e., rMSSD, low and high frequency power and its ratio, SD1 and SD2). Exercise heart rate was calculated by recording the area under the curve (AUC) response. Internal session load was evaluated 30 min after each session. Blood concentrations of creatine kinase and lactate dehydrogenase were analyzed before the first visit and 24 h after the last sessions. Results: The CWI group presented higher rMSSD than the control group at each time point (group-effect P = 0.037). The SD1 was higher in CWI group when compared to the control group following the last exercise session (interaction P = 0.038). SD2 was higher in CWI group compared to the control group at each time point (group-effect P = 0.030). Both groups presented equal CMJ performance (P > 0.05), internal load (group-effect P = 0.702; interaction P = 0.062), heart rate AUC (group-effect P = 0.169; interaction P = 0.663), and creatine kinase and lactate dehydrogenase blood concentrations (P > 0.05). Conclusion: Repeated post-exercise CWI improves cardiac-autonomic modulation. However, no differences in neuromuscular performance, muscle damage markers, or session internal load were demonstrated between the groups.
Keywords: Cryotherapy; Heart rate variability; Ice bath; Ice immersion; Running training